2015
DOI: 10.7314/apjcp.2014.15.23.10475
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Expression Analysis Suggests Functional Overlapping of Human FOX Transcription Factors in Cancer

Abstract: Forkhead-box (FOX) transcription factors comprise a large gene family that contains more than 50 members in man. Extensive studies have revealed that they not only have functions in control of growth and development, but also play important roles in different diseases, especially in cancer. However, biological functions for most of the members in the FOX family remain unknown. In the present study, the expression of 39 FOX genes in 48 kinds of cancer was mined from the Gene Expression Atlas database of Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Genetic analyses indicated that many of these FOX genes are differentially expressed in a variety of diseases, including cancer 1 - 8 . Several FOX subfamilies, such as FOXA, FOXC, FOXM, FOXO and FOXP, are associated with tumorigenesis and cancer progression, playing roles as either oncogenes or tumor suppressors, depending on the family member and cell type 1 , 2 , 9 .…”
Section: Introduction: Overview Of Fox Proteins In Cancermentioning
confidence: 99%
“…Genetic analyses indicated that many of these FOX genes are differentially expressed in a variety of diseases, including cancer 1 - 8 . Several FOX subfamilies, such as FOXA, FOXC, FOXM, FOXO and FOXP, are associated with tumorigenesis and cancer progression, playing roles as either oncogenes or tumor suppressors, depending on the family member and cell type 1 , 2 , 9 .…”
Section: Introduction: Overview Of Fox Proteins In Cancermentioning
confidence: 99%
“…Due to the large number of FOX families, we focused on the key components of six subfamilies in this study. Studies have found that FOXA1, FOXM1, FOXO3, FOXP1 and so on play an important role in tumors as oncogenes or tumor suppressor genes (11).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Over the past few years, deregulation of FOX proteins has been demonstrated to contribute to the pathogenesis of a variety of diseases, including glaucoma, language disorders, and cancers. [8][9][10] Genetic analyses have indicated that a loss or gain of FOX function might be implicated in promoting tumorigenesis as well as cancer progression. 11 As a consequence, FOX proteins are considered as direct or indirect targets for therapeutic intervention of cancers, as well as biomarkers for predicting and monitoring treatment responses.…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box (FOX) proteins are a large family of transcription factors, which have complex and important functions in multiple biological processes, such as cell‐cycle control, cell differentiation, proliferation and development . Over the past few years, deregulation of FOX proteins has been demonstrated to contribute to the pathogenesis of a variety of diseases, including glaucoma, language disorders, and cancers . Genetic analyses have indicated that a loss or gain of FOX function might be implicated in promoting tumorigenesis as well as cancer progression .…”
Section: Introductionmentioning
confidence: 99%